2009
DOI: 10.5457/ams.128.09
|View full text |Cite
|
Sign up to set email alerts
|

Leukocytes, C-Reactive Protein and Interleukin-6 in Acute Appendicitis in Children: Diagnostic Value and Association with Histological Findings

Abstract: <p><strong>Background:</strong> Many efforts have been made to find diagnostic tools that would help select children with clinical signs of acute appendicitis that would need immediate appendectomy and to find tools that would reduce the numbers of negative appendectomies.</p><p><strong>Aim:</strong> We aimed to show the association between leukocyte count, level of C-reactive protein and interleukin-6 in peripheral blood on the one side and the degree of histological … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Furthermore, the presence of a fecalith causes luminal obstruction, distention, and inflammation of the appendix wall, resulting in suppurative transmural inflammation, ischemia, infarction, and perforation of the appendix [ 20 ]. Numerous studies demonstrated that cytokines (e.g., interleukin-6 (IL-6)) [ 21 ] or acute phase proteins (e.g., CRP) could be used to predict the AA [ 1 ], control the severity of disease, and detect any complications [ 22 ]. Therefore, community-acquired intra-abdominal infection and inflammation play a significant role in the development of AA.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the presence of a fecalith causes luminal obstruction, distention, and inflammation of the appendix wall, resulting in suppurative transmural inflammation, ischemia, infarction, and perforation of the appendix [ 20 ]. Numerous studies demonstrated that cytokines (e.g., interleukin-6 (IL-6)) [ 21 ] or acute phase proteins (e.g., CRP) could be used to predict the AA [ 1 ], control the severity of disease, and detect any complications [ 22 ]. Therefore, community-acquired intra-abdominal infection and inflammation play a significant role in the development of AA.…”
Section: Discussionmentioning
confidence: 99%